Doctor Who : the Tenth Doctor. Volume 4, The endless song - Abadzis, Nick (Titan Comics, a division of Titan Publishing Group, 2016)
The Tenth Doctor and Gabriella Gonzalez set off on a bold new journey! Whether facing an evil corruption of sentient music on a gas giant, journeying back to the dawn of humankin, or battling disc-like gladatorial captors in a millennia-old free-for-all, there are no limits to the cosmic adventure - or the mortal danger!